Quality of Life in Primary Biliary Cholangitis - Advances in the Treatment - Kuzio, Agnieszka; Cieplińska , Aleksandra; Jama, Grzegorz; Ziojła-Lisowska, Kinga; Pliszka, Marzena; Piasecka, Zuzanna; Haczkur-Pawłowska, Karolina; Borowiak, Maciej; Kolano, Patrycja; Karnas-Bogacka, Patrycja (Quality in Sport, 2024)
Primary sclerosing cholangitis (PSC) is an inflammatory, cholestatic and progressively fibrotic liver disease devoid of effective medical intervention. PBC is a presumed immune-mediated liver disease of middle-aged women associated with significant morbidity and mortality. People living with PBC are frequently symptomatic, experiencing a quality-of-life burden dominated by fatigue, itch, abdominal pain, and sicca complex. Many drugs have been studied for treatment, including agents with choleretic and immunosuppressive properties. Future PBC licensed therapy will likely include peroxisome proliferator activated receptor (PPAR) pathway agonists, including specific PPAR-delta agonism (seladelpar), as well as elafibrinor and saroglitazar (both with broader PPAR agonism). Effective therapy reduces the need for transplantation and improves life expectancy.